Prediction of Unemployment Rates in East Java Region Using Multiple Linear Regression Method - Muhammad Farhan Alauddin; Sentot Achmadi; Joseph Dedy Irawan (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2025)
Unemployment is a major problem for developing countries, including Indonesia. The average unemployment rate in East Java is 5.202 percent from 2004 to 2023, according to data from Badan Pusat Statistik (BPS). These figures show that unemployment is still a major problem for local governments, despite changes. The purpose of this study is to create an application that can predict the number of unemployed in the future. The method used is multiple linear regression where this method was chosen because it can show how the year and labor force participation rate, which are two independent variables, correlate with the unemployment rate as the dependent variable. The data used comes from BPS and covers 19 years. This prediction model is integrated into a web-based platform to make the research results easier to access and use. This platform will display data and analysis results interactively, so that it can be used by local governments, academics, and other individuals looking for information about unemployment. The results of the study show that the regression model created is quite accurate. Based on the results of testing that has been carried out on the existing features, the system has displayed the appropriate output.